Социализация и самореализация студентов в системе воспитательной работы колледжа - Жумалиева, Г.Г. (My University, 2013)
In the report focus on issues of youth education in the pedagogical college after Zh.Dosmukhamedov. There are 23 different circles and 6 clubs, which occupies 75% of the students. The main purpose of educational institution - to ensure the professionalization and educate professionals able to work in the new socio - economic conditions.Proper organization of leisure of students, young people need to know themselves better. Their participation in sports clubs, circles have a very important mission, which includes the formation of civic, moral –patriotic education, creative and physical abilities, educates young people, owning culture intellectuals, professionally competent person who knows the culture and history of their country. Creativity recognized how to fill people's lives with meaning and joy, socially and personally meaningful content.